Investigating factors that affect older adults' technology acceptance in Singapore context based on STAM - Chew, Hong Ern (Nanyang Technological University, 2024)
Purpose: This research seeks to explore how older adults in Singapore embrace technology, scrutinizing the elements linked to their acceptance of it. By utilizing the Senior Technology Acceptance Model (STAM), the study strives to comprehend and tackle the distinct obstacles they encounter in this digital era. The ultimate goal is to encourage their continual engagement in our progressively digital world.